Responsibility to Protect sebagai Bentuk Perlindungan Hak Asasi Manusia di ASEAN - Norilla Norilla; Eddy Mulyono (University of Jember, 2018)
Association of Southeast Asian Nations (ASEAN) established on August 8, 1967 still accords to the principle of non-intervention which has been arranged in the ASEAN Charter. This principle, however, has been debated among ASEAN members, specifically when it is dealt with human rights. While the instutionalization is one of ASEAN’s achievements, human rights become one of pivotal issues in Southeast Asia which subsequently raises questions on the commitment of ASEAN to support the Responsibility to protect at the Summit on 2005. This article revisits the responsibility to protect in international law which is accorded to international customary law of Article 38 paragraph (1) of the Statute of International Court of Justice (ICJ). By using legal research, this article asserts that the responsibility to protect is essentially applicable to be adopted by regional intergovernmental organization like ASEAN, though it was initially only adopted by the Security Council of the United Nations. But, the principle of non-intervention would be the primary barrier to applying it. Therefore, this article recommends to wielding power to the Security Council of the United Nations with respect to solving such problem at the ASEAN level with the following idea to include ASEAN as the UN member. Keywords: Responsibility to protect, Human Rights, ASEAN